Pembuatan Lilin Pengharum Ruangan Aroma Terapi dari sabun yang Bernilai Ekonomis - Masriadi; Maharani; Musalas Fatih; Sapar; Ilham Taheir; Ratna (Insan Kreasi Media, 2023)
Making Aromatherapy Candles from Economically Valued Soap. The purpose of the student creativity program – entrepreneurship (PKM-K) The use of soap as a room freshener candle that has economic value is to provide innovative and creative ideas for improvement. Implementation methods used are input, process (production), output, and evaluation. The results of this program are input, conducting market surveys to determine market conditions. Next is a feasibility study of the business to be run. The last stage is the selection of materials and the provision of places as well as facilities and infrastructure to support the production process. Process (production), the process of making Air Freshener Candles starting from the preparation of materials and tools until the Air Freshener Candles are ready to be marketed. Output, namely the handicrafts made of Air Freshener Candles that are ready to be used and marketed to consumers. The last is evaluation, that is, this stage is carried out when product production has been completed. At this stage, we will review any deficiencies that make consumers uncomfortable using our products. The conclusion of the PKM-K program is Aromatherapy Room Fragrance Candles from Economically Valued Soap which presumably can create business opportunities for students.